Why? : what makes us curious - Livio, Mario, 1945- (New York : Simon & Schuster, 2017)
Author Mario Livio explores the origin and mechanisms of human curiousity.
Curious -- Curioser -- And curioser -- Curious about curiosity: information gap -- Curious about curiosity: intrinsic love of knowledge -- Curious about curiosity: neuroscience -- The rise of human curiosity: a brief account -- Curious minds -- Why curiosity?
Includes bibliographical references (p. 197-237) and index.
Adult
Adult
Keywords: Curiosity -- History; Curiosity -- History